2020
DOI: 10.1016/j.heliyon.2020.e04628
|View full text |Cite|
|
Sign up to set email alerts
|

New surgical technique of laparoscopic resection of adenomyosis under real-time intraoperative ultrasound elastography guidance: A case report

Abstract: Detecting adenomyosis in the myometrium is a challenge since it is infiltrative with ill-defined margins and can be often confused with uterine fibroids. However, recent advances, such as ultrasound elastography, have enabled its detection in the myometrium, thereby facilitating its accurate diagnosis. We report our experience of performing complete laparoscopic resection of adenomyosis under real-time ultrasound elastography guidance in a 32-year-old woman who underwent laparoscopic adenomyomectomy following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…We recently reported a case of subtype I adenomyosis treated using laparoscopic, conservative excision with intraoperative real-time elastography. After resection of the adenomyosis, the lesion was visualized using elastography, and the boundary between the adenomyosis and the normal myometrium was carefully and tactilely resected with scalpel and scissor forceps without using a power instrument, such as harmonic scalpels, such that only the adenomyosis lesion was being completely resected [18]. In this case, we used cold scalpels instead of a power instrument because prior experience demonstrated that electrosurgery induced thermal denaturation and prevented distinguishing between the adenomyosis and the normal endometrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported a case of subtype I adenomyosis treated using laparoscopic, conservative excision with intraoperative real-time elastography. After resection of the adenomyosis, the lesion was visualized using elastography, and the boundary between the adenomyosis and the normal myometrium was carefully and tactilely resected with scalpel and scissor forceps without using a power instrument, such as harmonic scalpels, such that only the adenomyosis lesion was being completely resected [18]. In this case, we used cold scalpels instead of a power instrument because prior experience demonstrated that electrosurgery induced thermal denaturation and prevented distinguishing between the adenomyosis and the normal endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The boundary between the adenomyosis and the normal myometrium was indistinct and could not be palpated with a power instrument, such as a harmonic scalpel. Therefore, we used a #11 scalpel as in our previous study [18] since the adenomyosis and the normal myometrium can be easily distinguished with a scalpel. A longitudinal incision was made in the uterine serosa, and the adenomyosis lesion was nucleated (Figure 3a,b).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Zheng et al found that resection combined with LNG-IUD was more effective in reducing menstrual flow when compared to the IUD alone ( p < 0.001), but no difference in pain reduction was noted ( p = 0.061) [ 59 ]. A case report by Ota et al was recently published investigating a new technique using real-time intraoperative ultrasound elastography guidance during laparoscopic resection of adenomyosis to preserve healthy uterine tissue while avoiding residual disease in the myometrium [ 60 ].…”
Section: Resltsmentioning
confidence: 99%
“…Безліч нових технічних розробок з успіхом доповнюють інформацію, отриману під час УЗД: це, зокрема, поєднання B-режиму з кольоровим і спектральним доплерівським, створення 3D і 4D зображень при мультипараметричному УЗД [15,21,22,25]. Проте висока частота діагностичних помилок (20-40%), залежність деталізації структури міометрія і параметрів сонографіч-ного диференціювання аденоміозу від досвіду оператора і апаратури сприяють пошуку нових оптимальних методів діагностики [19].…”
Section: вступunclassified